IMPLEMENTASI TADARRUS MUWAJJAH DALAM MENINGKATKAN BACA AL-QUR’AN MAHASISWI INTENSIF - Izzat Amini; Nurul Hasanah; Luthfatul Qibtiyah (Dirosat : Journal of Islamic Studies, 2022)
The science of recitation is a science about the rules and procedures for reading the Qur'an properly which aims to keep us from reading the Qur'an incorrectly. Therefore, this study aims to find out how the implementation, constraints and solutions of the implementation of lead recitation in improving the reading of the Qur'an for intensive students in the third semester at IDIA Prenduan. This research uses a qualitative approach with the type of field study research. The results of this study are: 1) the form of the implementation of lead recitation begins with reading a prayer, mudabbiroh asking for the previous material, listening to the reading of the Qur'an and asking students the law of recitation, and improving the reading of the Qur'an, and the last closed by reading the prayer khotmil Qur'an. 2) Obstacles and solutions from the implementation of these activities, namely: a) The perspective of mudabbiroh, less effective time and lack of interest in learning by students. The solution to overcome this is for the supervisor to come on time and motivate students to be enthusiastic about learning by choosing learning strategies that are suitable for students. b) The perspective of students, less effective time and lack of readiness to learn.